Third World Studies Center Fortieth Anniversary: Directors' Forum - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies, 2018)
Proceedings of the forum of former TWSC directors during the fortieth anniversary conference of the UP Third World Studies Center, 9-10 February 2017.